2011
DOI: 10.1002/asi.21688
|View full text |Cite
|
Sign up to set email alerts
|

Mapping world scientific collaboration: Authors, institutions, and countries

Abstract: International collaboration is being heralded as the hallmark of contemporary scientific production. Yet little quantitative evidence has portrayed the landscape and trends of such collaboration. To this end, 14,000,000 documents indexed in Thomson Reuters's Web of Science (WoS) were studied to provide a state-of-the-art description of scientific collaborations across the world. The results indicate that the number of authors in the largest research teams have not significantly grown during the past decade; ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
207
0
11

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 309 publications
(250 citation statements)
references
References 56 publications
13
207
0
11
Order By: Relevance
“…The USA was in the second position in terms of collaboration with Arab world. As the most contributor in scientific research at global level, USA sustains to be a major contributor in the scientific collaborations (Gazni et al 2012). Germany and UK were also among the top collaborators in research with Arab world.…”
Section: Resultsmentioning
confidence: 99%
“…The USA was in the second position in terms of collaboration with Arab world. As the most contributor in scientific research at global level, USA sustains to be a major contributor in the scientific collaborations (Gazni et al 2012). Germany and UK were also among the top collaborators in research with Arab world.…”
Section: Resultsmentioning
confidence: 99%
“…Collaboration in science highlighted increased partnerships between scientific advanced and emergent countries in terms of co-authoring scientific papers (Adams 2013), as well as at the global level (Wagner et al 2015). That translates in strong benefits for participating countries (GlĂ€nzel 2001) and institutions (Gazni et al 2012) in terms of citations. Collaboration for mutual benefit has also gained increasing acceptance, with ''partner'' selection becoming a strategic priority to enhance one's own production (Chinchilla-RodrĂ­guez et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Multi-author research has become more common (Gazni, Sugimoto, & Didegah, 2012;Persson, GlĂ€nzel, & Danell, 2004) and receives more citations than does solo research (Gazni & Didegah, 2010;Sooryamoorthy, 2009; Leimu & Koricheva, 2005a&b). However, a few studies have found no correlation between more authors and increased citations (Bornmann, Schier, Marx, & Daniel, 2012;Haslam et al, 2008).…”
Section: Research Collaborationmentioning
confidence: 99%